Art therapy and brain injury: making the invisible visible - Wolf, Denise R.; Rattigan, Michele D. (Frontiers in Psychology, 2024)
The multiple cognitive, somatic, and behavioral changes following head injuries can result in expressive language difficulties that may not be resolved quickly. This paper explores the traumatic brain injury and post-concussive syndrome artwork created by an art therapist and the child of an art therapist, making the invisible neurological consequences of head injuries visible.between patients, health professionals, and family members. Utilizing client imagery as a form of communication may improve patient outcomes through the identification and resultant treatment of overlooked and underdiagnosed symptoms. Experiences such as confusion, fear, localized pain, and mood lability stem not only from the injury itself, but from the experience of damaged microstructures that are often undetectable in standard diagnostic testing. Additionally, symptoms such as temperature and appetite dysregulation, vestibular and proprioceptive disruptions, and circadian rhythm sleep disorders evade standard diagnostic inventories. This may prompt the patient to question the reality of their somatic and cognitive experiences.Research supports the position of the authors: these experiences can be communicated through